What lies beneath [videorecording (DVD)] - Ford, Harrison, 1942-; Pfeiffer, Michelle, 1957-; Morton, Joe, 1947- (Paramount, 2017)
Claire reports hearing voices and witnessing eerie occurrences in and around her home, including seeing the face of a young woman reflected in water.